2016
DOI: 10.1007/s10508-016-0823-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Sexual Aggression Victimization and Perpetration Among Polish University Students: A Longitudinal Study

Abstract: This two-wave study investigated predictors of sexual aggression victimization and perpetration in a convenience sample of 318 Polish university students (214 women), considering males and females from the perspective of both victims and perpetrators. At T1, we assessed participants' risky sexual scripts (defined as cognitive representations of consensual sexual interactions containing elements related to sexual aggression), risky sexual behavior, pornography use, religiosity, sexual self-esteem, and attitudes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 60 publications
13
59
0
Order By: Relevance
“…Unchecked exposure to pornographic movies and sexual contents leads, according to the interviewed adolescents, also to blackmail, sexual harassment, and sexual abuse. These behaviors have also been found in other studies of youth throughout the world [ 12 , 59 , 69 ] and in the Arab society in particular.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Unchecked exposure to pornographic movies and sexual contents leads, according to the interviewed adolescents, also to blackmail, sexual harassment, and sexual abuse. These behaviors have also been found in other studies of youth throughout the world [ 12 , 59 , 69 ] and in the Arab society in particular.…”
Section: Discussionsupporting
confidence: 78%
“…Studies have shown that the nature of sexual discourse, its culture, and the way it is managed have a predictive correlation with the actual behavior of adolescents and adults [ 11 , 12 ]. The absence of overt sexual discourse also leads to ignorance [ 13 ], fears, and anxiety in Arab adolescent boys and girls.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in a two-wave study (separated by a year) of Polish university students, additional data were provided suggesting a role for pornography use in predicting attitudes and behaviors. Tomaszewska and Krahé (2018) found that pornography use assessed at Time 1 predicted sexual aggression perpetration in the subsequent 12month period via its association with sexual aggression perpetration since the age of 15. The researchers also found that pornography use at Time 1 significantly predicted attitudes supporting sexual coercion, which had a direct prospective link to perpetration 12 months later.…”
Section: Longitudinal Studies (See Cell 4b Of Table 2)mentioning
confidence: 89%
“…The same process of script learning, development, and use applies to aggression‐related scripts and media violence (Huesmann, ). For example, pornography use has been linked to risky sexual scripts and coercive sexual behavior (e.g., Tomaszewska & Krahé, ).…”
Section: Media Violence and Aggression: Well‐known Pathsmentioning
confidence: 99%